Coupling of spectral characteristics of pigmental composition and structural indicators of phytoplankton in Svisloch river - Mikheeva, Tamara M.; Smolskaya, Volha S.; Savich, Iryna V.; Zhukava, Hanna A. (Journal of the Belarusian State University. Ecology, 2019)
Studies on the River of Svisloch were aimed at assessing the quantitative and qualitative characteristics of the autotrophic component of plankton, as well as the search for their correlation with the data of the spectral analysis of the pigment composition. It is shown that pigment indices Е450/Е480, Е480/Е664, Е430/Е664, Е430/Е412 can be used to characterize the structural indicators of phytoplankton, and therefore reflect the state of planktonic producers in the ecosystem. Also, during the preliminary analysis, auxiliary pigment indices of extract purity and clarity of the prescribed spectrum were calculated: Е664/Е720, Е430/Е720, Е530/Е720, Е430/Е530 and Е664/Е530. A close interrelation was found between the index E450/E480 and the share of cyanobacteria in the total phytoplankton biomass (r = –0,81), and, on the contrary, the positive correlation of this index with the share of green algae (r = 0,72) and diatoms (r = 0,73).